What are the Forms and Obstacles of Community Participation in Environmental Damage Prevention? - Siti Mariyam; Adhi Putra Satria; M. Samsudin (Administrative and Environmental Law Review, 2023)
This research examines the national and international legal frameworks governing community involvement in environmental damage prevention and the challenges and various forms of community participation in environmental damage prevention efforts globally. This study uses a qualitative method to conduct normative legal research, which involves a literature review of various international legal instruments and field cases related to community participation in the prevention of environmental damage and uses Seherly Arnenstein's theory of community participation to examine community participation in environmental conservation. The results show that community participation in preventing environmental damage has a legal position at the national and international levels. At the international level, several agreements, such as the United Nations Framework Convention on Climate Change (UNFCCC), the Convention on Biological Diversity (CBD), and the Basel Convention, have established a legal framework for preventing environmental damage, including community participation. Meanwhile, at the national level, Law No. 32/2009 on Environmental Protection and Management (UU PPLH) has regulated the rights and obligations of the community in protecting the environment. Furthermore, this study found that community participation in preventing environmental damage can be done through various means, such as decision-making processes, access to environmental information, and participation in implementing environmental policies. However, there are still challenges and obstacles in its implementation, such as limited access to information, lack of public awareness, and lack of government and private sector support. Based on this, more significant efforts are needed to strengthen community participation in preventing environmental damage, including increasing access to environmental education and information and establishing more active and effective forums for community participation. The active involvement of the government, civil society organizations, and private institutions is needed to ensure that community participation in preventing environmental damage can be achieved.